Women's participation in scientific and technical fields in Malaysia - Mat Daud, Nuraihan (IIUM Press, International Islamic University Malaysia, 1999)
The scientific and technical fields are generally dominated by men. Women tend to shy away from using technical devices and from trying to understand the principles behind their operation. One of the major reasons for their seemingly lack of interest is the lack of encouragement from their family and society. This paper discusses the steps taken by a country, namely, Malaysia, to encourage its female population to venture into this area. Policies were created by the government for this purpose. Great emphasis is given on education, which is one of the important factors influencing one's choice of vocation. In its process of restructuring the society, the government has effectively increased the involvement of women particularly the Muslims in the professional and technical fields as the vast opportunities are provided for them to pursue their studies in this area. There is a marked increase in the number of female student intake in technical and vocational institutions. There is also an increase in the number of females in related fields such as accountancy, engineering, architecture and medicine. The ratio of male to female involvement has however not changed much when the figures are analysed.